2022
DOI: 10.1093/jacamr/dlac121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceftazidime/avibactam plus fosfomycin combination on 30 day mortality in patients with bloodstream infections caused by KPC-producing Klebsiella pneumoniae: results from a multicentre retrospective study

Abstract: Introduction The primary outcome of the study was to evaluate the effect on 30 day mortality of the combination ceftazidime/avibactam + fosfomycin in the treatment of bloodstream infections (BSIs) caused by KPC-producing Klebsiella pneumoniae (KPC-Kp). Materials and methods From October 2018 to March 2021, a retrospective, two-centre study was performed on patients with KPC-Kp BSI hospitalized at Sapienza University (Rome) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Similarly, CZA susceptibility rate was not documented in three studies ( 49 , 50 , 55 ), as well as it was found as 89.5% and 79% in two studies, respectively ( 57 , 61 ). More than half of the studies had CRE infections, while six included CRKP infections ( 15 , 52 54 , 56 , 60 ). MDR/XDR-PA infections were assessed only in one study ( 57 ) and two studies included mixed types of infections caused by CRE or carbapenem-resistant P. aeruginosa (CRPA) and CRE or MDR-PA, respectively ( 49 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, CZA susceptibility rate was not documented in three studies ( 49 , 50 , 55 ), as well as it was found as 89.5% and 79% in two studies, respectively ( 57 , 61 ). More than half of the studies had CRE infections, while six included CRKP infections ( 15 , 52 54 , 56 , 60 ). MDR/XDR-PA infections were assessed only in one study ( 57 ) and two studies included mixed types of infections caused by CRE or carbapenem-resistant P. aeruginosa (CRPA) and CRE or MDR-PA, respectively ( 49 , 51 ).…”
Section: Resultsmentioning
confidence: 99%
“… 39 Ceftazidime/avibactam in combination with fosfomycin has been used successfully in patients with KPC- Kp bloodstream infections and is associated with reduced recurrence and secondary infection rates compared with treatment with ceftazidime/avibactam alone. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Perdigao Neto et al, described a prospective series of 13 patients (treated with fosfomycin) who had infections (BSI, n=11) due to β-lactams and colistin-resistant gram-negative bacteria ( K. pneumoniae , n=9), and they showed that meropenem (82% synergism via time-kill assay) was the most commonly used antibiotic in combination with fosfomycin (n=10), with a cure rate of 70% 10 . Oliva et al, evaluated the effect of the ceftazidime/avibactam plus fosfomycin combination in the treatment of BSIs caused by CRKP, and although there was no difference in 30-day overall mortality, they showed a lower rate of subsequent CRKP or secondary infections than other ceftazidime/avibactam-based regimens in fosfomycin combination group 11 . In our study, we also found no statistically significant difference in 14- and 30-day mortality among different types of combination regimens such as one or two antibiotic combinations, meropenem-containing regimens, colistin/polymyxin B-containing regimens, and aminoglycoside-containing regimens.…”
Section: Discussionmentioning
confidence: 99%